2017
DOI: 10.1007/s00203-017-1362-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anaerobiasis or Hypoxia on Pseudomonas aeruginosa Inhibition of Aspergillus fumigatus Biofilm

Abstract: Pseudomonas aeruginosa (Pa) and Aspergillus fumigatus (Af) are the major bacterial and fungal pathogens in the airways of cystic fibrosis (CF) patients. This is likely related to their ability to form biofilms. Both microbes have been associated with CF disease progression. The interplay between these two pathogens has been studied under aerobic conditions, though accumulating data indicates that much of the CF airway is hypoxic or anaerobic. We studied the microbial interaction in these latter environments. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 55 publications
3
28
0
Order By: Relevance
“…When experiments were repeated under hypoxic conditions, we observed the same outcomes, with pyoverdine being the principal mediator of antifungal activity on both forming and preformed A. fumigatus biofilms. This is consistent with our previous observations with nonmutant P. aeruginosa cells and filtrates under hypoxic conditions (74). As CF progresses, P. aeruginosa mutants frequently appear, and commonly these mutants are hypoproducers of pyoverdine (39).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…When experiments were repeated under hypoxic conditions, we observed the same outcomes, with pyoverdine being the principal mediator of antifungal activity on both forming and preformed A. fumigatus biofilms. This is consistent with our previous observations with nonmutant P. aeruginosa cells and filtrates under hypoxic conditions (74). As CF progresses, P. aeruginosa mutants frequently appear, and commonly these mutants are hypoproducers of pyoverdine (39).…”
Section: Discussionsupporting
confidence: 93%
“…Loaded plates were incubated at 37°C for 24 h. On the agar, hyphal mats with biofilm form (48), as verified by optical microscopy, showing the same arrangement as has been studied in liquid wells, studied by optical, confocal, and electron microscopy (29,83). Studies were also conducted in a hypoxic environment, as detailed previously (74). In brief, the assay plates were incubated in the Gas-Pak EZ Campy pouch system (Becton Dickinson, Franklin Lakes, NJ), generating an atmosphere of 10% oxygen (74).…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Except in our studies shown where PQS was titrated to study biological effects of various concentrations, in our other studies pilot experiments were performed with a range of PQS concentrations, dose effects, if any, observed, and only extensive studies with single selected concentrations are shown. As previous studies [17, 18, 38, 39] suggested metabolism of preformed Af biofilm is less susceptible to a variety of biological perturbations than metabolism of forming biofilm, in general higher PQS concentrations were initially selected for studies of preformed biofilm.…”
Section: Methodsmentioning
confidence: 99%
“…Studies under hypoxic conditions were performed using BD GasPak EZ Campy Pouch System (BD, Franklin Lanes, NJ) to contain the plates as previously described, producing an atmosphere of 10 % oxygen [39].…”
Section: Methodsmentioning
confidence: 99%